Analisis Penjadwalan Proyek Gedung Bertingkat Menggunakan Metode CPM (Critical Path Method) dan PERT (Program Evaluation and Review Technique) (Studi Kasus: Proyek Pembangunan Tahap 1 Rumah Sakit Muhammadiyah Gresik) - Karina Aulia Rahma; Zetta Rasullia Kamandang (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Time and cost are important and interrelated in the implementation of construction project activities. In the world of construction project that can be used as a measure of a project’s success is if the projet=ct can run according to the planned schedule with allocated costs in accordance with the quality of the materials used. The result of the analysis show that the CPM method is more efficient in terms of time and coast. The result of calculating the duration and cost of the CPM method produce a duration of 117 days with an allocated cost pf IDR 5.951.026.616, which is 19 days faster with a cost difference of IDR 307.764.792 compared to the PERT method. This research was conducted according to the calculation of the initial smart time of the project, namely on May 16, 2022 according to real sata. In the analysis in this study, scheduling planning using the CPM and PERT method was applied with the aim of knowing which method is more efficient in terms of time and cost.